The influence of crown-to-implant ratio in single crowns on clinical outcomes: A systematic review and meta-analysis - Pellizzer, Eduardo Piza [UNESP]; Marcela de Luna Gomes, Jéssica [UNESP]; Araújo Lemos, Cleidiel Aparecido [UNESP]; Minatel, Lurian [UNESP]; Justino de Oliveira Limírio, João Pedro [UNESP]; Dantas de Moraes, Sandra Lúcia (My University, 2020)
Statement of problem: A consensus about the effect of crown-to-implant (C/I) ratio in single crowns regarding the implant survival rate and marginal bone loss (MBL) is lacking. Purpose: The purpose of this systematic review and meta-analysis was to evaluate the influence of C/I ratio in implant-supported single crowns on clinical outcomes. Material and methods: The search was made in the PubMed/MEDLINE, Scopus, and the Cochrane Library databases following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria and registered with the International Prospective Register of Systematic Reviews (PROSPERO: CRD42018095711). The focused question was “Does the crown-to-implant ratio influence clinical outcomes for implant-supported single crowns?” Results: Five direct comparative studies were included (C/I ratio ≤1 or >1, or ≤2 or >2), including a total of 262 participants with a mean age of 54.5 years. The meta-analysis comparing C/I ratio between ≤1 or >1 revealed no significant differences (P=.18; risk difference:-0.05; 95% confidence interval: -0.11 to 0.02) in terms of implant survival rate; the same was true for C/I ratio between <2 or ≥2 (P=.05; risk difference:-0.06; 95% confidence interval: -0.12 to -0.00), both analysis were made with a mean follow-up period was 36 months. The mean MBL was calculated based in the qualitative data for each C/I ratio: ≤1 (0.15 mm [-0.34 to 0.34]); >1 (0.07 mm [-0.29 to 0.22]); <2 (1.32 mm [0.38-0.9]); and ≥2 (1.37 mm [-0.02 to 0.91]). The qualitative data reported that the most common mechanical complication was screw loosening, and the most common biological complication was peri-implantitis. Conclusions: The meta-analysis revealed no relationship between categories of C/I ratio for implant survival rate. The qualitative data also suggested that MBL increased as the C/I ratio increased.